Analysis of misconceptions on virus in the high school biology textbooks - P Mitha; M Ramli; Y Rinanto (Pascasarjana Universitas Pendidikan Indonesia, 2018)
One of the factors that impedes the process of acceptance and assimilation of new knowledge in students is misconception. The cause of misconceptions, one of which can be from textbooks used by teachers and students in learning. This study aims to analyze the type and percentage of misconceptions contained in biological textbooks. This research is a descriptive study with document analysis method, which is done by evaluating the concepts that already exist in the book carefully and comparing it with the reference books. Concepts that have been studied include the structure and characteristics of virus, classification of virus, replication of virus, and the role of virus in human life. Sample consist of three books selected purposively. This research used the instrument of misconception indicator in textbook according to Hershey. The results of the analysis on the three books, found that there are misconceptions on some of the virus concepts, i.e. 37% Under generalizations (UG), Obsoleted Concepts and Terms (OCT) by 12%, Oversimplifications (OS) by 8%, Overgeneralizations (OG) by 36%, and Misidentifications (MI) by 7%.